The Language of Counter-Arguments and Support Arguments in Argumentative Student Writing - Kaddoura, Noor Wafic (2021)
A Master of Arts thesis in Teaching English to Speakers of Other Languages (TESOL) by Noor Wafic Kaddoura entitled, “The Language of Counter-Arguments and Support Arguments in Argumentative Student Writing”, submitted in May 2021. Thesis advisor is Dr. Philip McCarthy. Soft copy is available (Thesis, Completion Certificate, Approval Signatures, and AUS Archives Consent Form).